127=(16*59.3/x)(16*9.9/x)

Simple and best practice solution for 127=(16*59.3/x)(16*9.9/x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 127=(16*59.3/x)(16*9.9/x) equation:


D( x )

x = 0

x = 0

x = 0

x in (-oo:0) U (0:+oo)

127 = ((16*59.3)/x)*((9.9*16)/x) // - ((16*59.3)/x)*((9.9*16)/x)

127-(((16*59.3)/x)*((9.9*16)/x)) = 0

127-150289.92*x^-2 = 0

-150289.92*x^-2 = -127 // : -150289.92

x^-2 = 0.00084503

-2 < 0

1/(x^2) = 0.00084503 // * x^2

1 = 0.00084503*x^2 // : 0.00084503

1183.38993882 = x^2

x^2 = 1183.38993882 // ^ 1/2

abs(x) = 1183.38993882^(1/2)

x = 1183.38993882^(1/2) or x = -1183.38993882^(1/2)

x in { 1183.38993882^(1/2), -1183.38993882^(1/2) }

See similar equations:

| p-8=-15/p | | -6x+7+7x=9 | | x-sqrt(11-10x)=-22 | | 10xwhat=990 | | 4x+6=4+3x | | 5t-9=31 | | 7k-5=30 | | 6a-5=43 | | -30-6a=2(1-7a) | | 7a^2-24a-4=0 | | 31+6n=-5(1-3n) | | 4(2)-3/2(1)-1 | | 2x+26=0 | | -9+2x+4x=9 | | 5x-6x-3=-5 | | 6+4(3-2n)=-4n+14 | | 1/6=1.5x | | 8y=-3x+4 | | 5b-2=18 | | 52x^3-122x^2+66x=0 | | -2n=6-2n | | -8x+8+5x=2 | | -3x+3=2 | | 6x+4.50y=45 | | 20.4/3.4= | | 2x/9-9/3=8-3x | | 6(x-2)+5x=9x-2(4-3) | | 9x+4=64 | | -7x+2y=70 | | .66x-6+3=4x-4 | | 4.5*4.4= | | 2x^2=2048 |

Equations solver categories